الشيخ محمد أشرف العظيم الآبادي ومنهجه في كتابه "عون المعبود" - Mesbahul Hoque; Kauthar Abd Kadir; Norzulaili Mohd Ghazali; Abdulloh Salaeh; Muneer Ali Abdul Rab (USIM Press, 2024)
This research aims to shed light on the book "Awn al-Ma'bood" by Sheikh Muhammad Ashraf al-Azim al-Abady; By answering two main questions; They are: Who is Sheikh Muhammad Ashraf Al-Azeem Al-Abady? And What is the method of his book "Awn Al-Ma'bood”? The research followed the analytical descriptive approach, and it reached a number of results related to the author and the book. First, Sheikh Muhammad Ashraf al-Azim al-Abady is the author of the book "Awn al-Ma'bood", there are those who made a mistake in the authorship of the book by attributing it to his older brother Shams al-Haq al-Azim Abadi, Second, this book is considered one of the best explanations of “Sunan Abi Dawud” in terms of methodology, in which the explanation of the hadiths avoiding lengthening and presenting them in the method of topical explanation, as well as dealing with the important things and aspects in explaining.